Practices Malaysian research universities: patent profile in the lens database / Mohd Arif Mohd Sarjidan ... [et al.] - Mohd Sarjidan, Mohd Arif; Abu Bakar, Azizi; Ismail, Noor Hidayati; Syed Omar, Sharifah Nur Syafiqah; Nordine, Noreena (Faculty of Information Management, 2023)
Patents are a valuable outcome of research activities in universities as a foundation for commercialization. The idea of transforming research work into products or services that are beneficial to the public has become the priority for almost all universities in the world. This paper focuses on the profile of patents produced by Malaysian Research Universities (MRU). The profiling considers the number of patents, stages of patents, collaboration effort for the patents, citation of the patents, and jurisdiction of the patents within 10 years from 2010 to 2020. The finding indicates that there is an association between patenting activities with the initiative by the government and the university ranking systems.